Avaliação temporal de uma comunidade bioincrustante atuando como armadilha para microplásticos - Motta, Daniel Gosser (2023)
Ecological succession is a natural and gradual process of changes in the structure and composition of a community, in which the form of colonization of the substrate and its respective biological interactions will be important factors in the creation or modification of an ecosystem. Biofouling or biofouling is the process of fixing micro and macro organisms on immersed consolidated substrates. Ecosystem engineers directly or indirectly influence the availability of resources, creating and modifying habitats and niches. Benthic communities represent one of the most important elements for assessing environmental quality and are particularly sensitive to different types of contaminants and pollutants, including plastics. These materials can have different sizes and when they reach 5mm to a few micrometers, they are called microplastics (MPs). Due to their geographic location, between rivers and waters, in addition to their proximity to urban areas, estuaries are regions highly impacted by the release of domestic and industrial effluents, being environments conducive to the accumulation of MPs. Unless better known, the relationship between fouling organisms and the presence of microplastics has not yet been studied, therefore, the present study aims to contribute to a better understanding of the relationship between the fouling community and microplastics present in the water column in a temporal analysis using silicone membranes as substrate. To this end, 6 membranes were collected and remained submerged in the Vitória Bay estuary, every 15 days, until they completed 90 days. The organisms and MPs associated with the membranes were sold in Petri dishes, where they were viewed under a magnifying glass, photographed and classified. The results show that the community acts as a trap for MPs, in addition to there being a positive difference between the exposure time of the membranes and the quantity of MPs.